Communication and teamwork in the therapeutic team is the basis of High quality medical services - Nalepa, Dorota; Weber, Dorota; Guz, Ewa; Mianowana, Violetta; Czekirda, Marta (Journal of Education, Health and Sport, 2017)
Introduction Communication between the physician and the nurse is one of the most important attributes in health care. Skilful organisation of social roles in order to improve patient care is key to effective communication. The division of labour should be assigned to a given person in such a way that the possessed skills minimise errors in the executed activities. In addition, assigning authority by a given organisation so as to identify the best candidate should be chosen consciously, therefore he/she is capable of making decisions in such a way that the patient remains unaffected. The aim of the study Showing the role of interpersonal communication in the relationship between the physician and the nurse in the hospital. Materials and Methods The investigation, using a questionnaire, was conducted in Provincial Specialist Hospital in Lublin in 2016. There were 88 surveys handed out (76 were returned, 2 were rejected due to lack of several answers), out of which seven for each job group underwent pilot studies. The statistical analysis was made using elements of descriptive statistics by calculating measures of cluster: mean, arithmetic, minimum, maximum, measures of dispersion, standard deviation. The connection between different characteristics was verified by means of chi-squared tests. Conclusions The impact of communication and the quality of treatment and care: More than 93% of the respondents were also satisfied with the mutual relationships with colleagues within the therapeutic team. Only 7% of the examined ones considered their relationship with work colleagues inappropriate. Almost all the test group agreed with the statement that a suitable relationship between the doctor and the nurse is important. Only single persons disagreed with this thesis or were unable to respond to it.